Caracterización físico-química del huevo del caimán llanero, crocodylus intermedius, graves 1819 - Morales-Arango, Julián; Duarte-Guerrero, Marcela; Zúñiga, Herly (Instituto de Ecología, A.C., 2007)
Some physicochemical characteristics of Crocodylus intermedius eggs were determined such as weight, morphometrics, specific gravity, shell thickness, quality and quantity of dense albumen, concentration of calcium and inorganic shell phosphorus, percentage of moisture in yolk and albumen, protein content and raw fat content. The results obtained were: weight (121.33 g), longitudinal longer diameter (84.12 mm), transversal longer diameter (51.64 mm), perimetral length (228.5 mm), perimetral width (173.17 mm), specific gravity (1.115-1.14), shell thickness in the wide pole (296.91 um), shell thickness in the narrow pole (275.91 um), shell thickness in the equatorial area (313.75 um), quantity and quality of dense albumen (73.7 Haugh units), concentration of inorganic calcium (43%), concentration of inorganic phosphorus (1.84%), percentage of humidity in albumen (91.24%), content of raw protein in yolk (18.54%), content of raw protein in albumen (6.68%), content of raw fat in yolk (19.30%). The results of the physico-chemical analyses of C. intermedius eggs are similar to those of different crocodilian species reported elsewhere.